Testing for strategy-structure fit and its importance for performance - Ana Aleksić; Sanda Rašić Jelavić (Management : Journal of Contemporary Management Issues, 2017)
Understanding different organizational elements, their mutual influence and creating congruence among them has been recognized as an important determinant of organizational performance. These complex interrelationships, and necessity of creating a fit between them, raises the question of how to align different organizational elements to contribute to overall organizational performance. In that sense, this paper addresses the issue of fit and, more specifically, analyses the presence and influence of strategy-structure fit on organizational performance. By using Miles and Snow typology, our goal was to capture and determine the pattern of relationships between strategy, structure, and strategy implementation processes and their influence on organizational performance. This paper presents results of a cross-sectional field research on a sample of 113 organizations in order to gain a better understanding of strategy-structure fit and its relation to performance. Results reinforce the existing literature and confirm the importance of fit among strategy, structure and strategy implementation process for higher levels of organizational performance.